Alterations in Blood Chemistry Levels Associated With Nipah Virus Disease in the Syrian Hamster Model. (20th November 2019) - Genzer, Sarah C; Welch, Stephen R; Scholte, Florine E M; Harmon, Jessica R; Coleman-McCray, JoAnn D; Lo, Michael K; Montgomery, Joel M; Nichol, Stuart T; Spiropoulou, Christina F; Spengler, Jessica R
Abstract: Nipah virus (NiV; family Paramyxoviridae, genus Henipavirus ) infection can cause severe respiratory and neurological disease in humans. The pathophysiology of disease is not fully understood, and it may vary by presentation and clinical course. In this study, we investigate changes in blood chemistry in NiV-infected Syrian hamsters that survived or succumbed to disease. Increased sodium and magnesium and decreased albumin and lactate levels were detected in animals euthanized with severe clinical disease compared with mock-infected controls. When subjects were grouped by clinical syndrome, additional trends were discernable, highlighting changes associated with either respiratory or neurological disease.